MANAGEMENT OF ENHANCING THE EFFICIENCY OF INVESTMENT USE IN THE AGRICULTURAL SECTOR FROM THE REPUBLIC OF MOLDOVA - Elena TIMOFTI; Aliona ȘARGO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The need for funding of the agricultural sector in recent years is growing in the situation when agricultural enterprises are consolidating in order to sell the produced products on domestic and international markets. On the one hand, there is a trend of land consolidation, and on the other hand, farmers want to buy all the tools and equipment necessary for carrying out their business. Heavy investments are made in inputs (quality seeds, fertilizers, animal varieties and breeds with high efficiency, etc.) and how these are mostly imported at world prices, the need for further funding increases. All these lead to the continuous growth of the need for financial resources. Another problem lies in the inefficient management of funding sources. With increasing investment in agriculture, Republic of Moldova faces constraints of implementation capacity. The research purpose is to analyze the efficiency of investment in agriculture and to determine the optimal level of investment for 1 ha of agricultural land.